UJI SIFAT FISIK DAN STABILITAS TABLET HISAP EKSTRAK ETANOL BUNGA ROSELLA (Hibiscus sabdariffa Linn) - Kayla Keysha Nathania; Dea Safila; Endah Ayu Nurul Badriah; Jasinca Arga Cetta Ramaniya; Selly Aufa Kusnil Laily (Jurnal Farmasi IKIFA, 2025)
Rosella (Hibiscus sabdariffa Linn) is a plant that has red petals with various health benefits such as being rich in natural antioxidants and anthocyanins, the flowers can be used as a vitamin for the body's immune system. The aim of this research is to develop a lozenge formulation based on rosella flower extract (Hibiscus sabdariffa Linn) by testing the physical properties and stability of the product. The lozenges are designed to provide an attractive taste and maximize the bioavailability of the active compounds. The lozenge formulation was carried out using the wet granulation method with additional ingredients. Testing of the physical properties of tablets includes organoleptic tests, weight uniformity tests, size uniformity tests, tablet friability tests, and tablet hardness tests. The testing of granule physical properties includes flow time test, angle of repose test and water content test. From the test, the organoleptic test results were pink with white spots. The weight uniformity test results showed an average tablet weight of 0.730 gr. The results of the size uniformity test have a diameter of 1.2 mm. In the tablet friability test, an average of 0.6% was obtained, and in the tablet dissolution time test, an average of 13.6 minutes was obtained.